The Mid-Infrared Instrument for the James Webb Space Telescope, VII: The MIRI Detectors. (4th January 2016) - Rieke, G. H.; Ressler, M. E.; Morrison, Jane E.; Bergeron, L.; Bouchet, Patrice; García-Marín, Macarena; Greene, T. P.; Regan, M. W.; Sukhatme, K. G.; Walker, Helen
Abstract: The MIRI Si:As IBC detector arrays extend the heritage technology from the Spitzer IRAC arrays to a 1024 × 1024 pixel format. We provide a short discussion of the principles of operation, design, and performance of the individual MIRI detectors, in support of a description of their operation in arrays provided in an accompanying paper. We then describe modeling of their response. We find that electron diffusion is an important component of their performance, although it was omitted in previous models. Our new model will let us optimize the bias voltage while avoiding avalanche gain. It also predicts the fraction of the IR-active layer that is depleted (and thus contributes to the quantum efficiency) as signal is accumulated on the array amplifier. Another set of models accurately predicts the nonlinearity of the detector-amplifier unit and has guided determination of the corrections for nonlinearity. Finally, we discuss how diffraction at the interpixel gaps and total internal reflection can produce the extended cross-like artifacts around images with these arrays at short wavelengths, ∼5 μm. The modeling of the behavior of these devices is helping optimize how we operate them and also providing inputs to the development of the data pipeline.